A Combined Theory of Change-Group Model Building Approach to Evaluating “Farm to Fork” Models for School Feeding in the Caribbean - Saint Ville, Arlette; Hickey, Gordon M.; Rouwette, Etiënne; Samuels, Alafia; Guariguata, Leonor; Unwin, Nigel; Phillip, Leroy E. (Frontiers in Sustainable Food Systems, 2022)
There is a scarcity of research on building nutrition-sensitive value chains (NSVCs) to improve diets and nutrition outcomes of populations in the Caribbean. This study contributes to filling this research gap by outlining a participatory approach to evaluating a NSVC model for “farm to fork” (F2F) school feeding in the Eastern Caribbean Island of St. Kitts. Using a combined group model building (GMB) and theory of change (ToC) approach, policy actors and other stakeholders across the school feeding value chain (n=37) were guided through a facilitated process to evaluate the ToC underlying a series of F2F interventions designed to enhance childhood nutrition. Stakeholders at the workshop engaged collaboratively to create a causal map of interconnected “system factors” that help explain behaviours contributing to unhealthy eating among children that extended well beyond the original F2F project ToC that had been used to inform interventions. Through this facilitated GMB process, stakeholders proposed additional food system interventions, and identified multiple “impact pathways” and “mediating influences” underlying local availability and consumption of nutritious foods in local school environments. Workshop participants were also able to identify leverage points where community-level efforts, alongside research interventions, may ensure that initiatives for building local NSVCs are ultimately institutionalized. Results of this study suggest that developing NSVCs for school feeding and food systems in the Caribbean requires both locally driven innovation and the leveraging of system-wide resources, with lessons for project intervention strategies.